Pengaruh Pemberian Insentif Kerja Terhadap Kinerja Karyawan pada PT Bank Syariah Bukopin Kantor Cabang Sidoarjo - TRIANSYAH, FEJRI (Jurnal Ekonomika dan Bisnis Islam, 2021)
AbstractThe sustainability and success of a company or organization can be seen from the performance owned by employees. Companies or organizations expect employees to complete tasks and generate information in a timely and accurate information. The company should also improve the factors that can affect employee performance. This research has a goal to know the effect of employment of incentives on employee performance. This research was conducted on PT. Bank Syariah Bukopin Branch Sidoarjo. The type of research used is quantitative. Technique of observation data collection, questionnaires and documentation. While the data analysis technique used is simple linear regression. The population of this research is all employees and managers of PT. Bank Syariah Bukopin Branch Sidoarjo to 93 people. The determination of the sample is done saturated sampling. As for the results of research on PT. Bank Syariah Bukopin Branch Sidoarjo that incentive administration has significant effect on employee performance. This can be seen from the results of statistical calculation of the hypothesis testing partially indicating that t count > t table, then Ha accepted and Ho rejected.